Penguatan Akhlak dan Kesehatan Mental Melalui Pendekatan Psikologi Keagamaan Pada Siswa MTs Kelas 8 di Pondok Pesantren Misbahul Khair - Mutiara, Yolanda; Prabowo, Muhammad Agung; Iqbal, Muhammad; Marti, Pipin Danu (Yayasan Daarul Huda Kruengmane, 2025)
This Community Service Program (PKM) was conducted to strengthen the moral character and mental well-being of 8th-grade MTs students at Pondok Pesantren Misbahul Khair through a religious psychology approach. Adolescents at the madrasah level are in a dynamic developmental stage marked by identity formation, the need for moral guidance, and heightened sensitivity to emotional and social pressures. Within the pesantren environment, integrating religious education with psychological support is essential for cultivating stable character, virtuous behavior, and strong mental resilience. Based on these needs, this PKM program was designed to provide comprehensive guidance that addresses students’ spiritual, behavioral, and psychological dimensions.This program employed a descriptive qualitative method through field observations, informal interviews, counseling sessions, group discussions, and the reinforcement of religious practices. The training materials included Islamic moral values, religious strengthening through daily worship, emotional regulation based on Islamic psychological concepts, and the development of healthy social interactions in accordance with Islamic principles. Additional activities such as Qur’an reading habits, thematic studies, and the cultivation of etiquette toward teachers and peers also contributed to the program. The results indicate positive changes in students’ attitudes and behaviors. They demonstrated improved understanding of noble character, greater discipline in performing religious obligations, and better emotional control and expression. The religious psychology approach further helped students recognize their emotional states and relate them to relevant spiritual values, resulting in a balanced relationship between religious understanding and mental health. The pesantren administration responded positively, acknowledging the program’s significant contribution to character formation and students’ psychological development.